The Prevalence of Cervical Rib Found During Chest Radiography in the Population of Khyber Pakhtunkhwa, Pakistan - Iftikhar, Shazia; Iftikhar, Zainab; Naz, Falak; Ahmad, Waqar; Rehman, Parkha; Javed, Mehvish; Sultana, Shagufta (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Objective: To find out the prevalence of cervical rib in the population of Khyber Pakhtunkhwa. Methodology: Study was conducted on data collected from various private practices of Khyber Pakhtunkhwa of 1038 postero-anterior chest radiographs where the patients were investigated for various conditions. Results: A total of 1038 chest radiographs that satisfied the inclusion criteria were examined in the current study. The study included 515 chest radiographs of males and 523 of females 15 to 75 years. Out of the 1038 cases, a total of 04 cases (0.38%) were found to be having cervical rib. The frequency of CR among males was found to be 01(0.09%) and that among females was 03(0.28%). Conclusion: In the current study the prevalence was 0.38% and was found mostly in females. As previous researches on cervical rib have shown that occurrence of cervical rib is due to mutations in Hox genes, so more studies need to be planned to confirm this connection. Also, the presence of cervical rib need to be well thought-out in different medical specialties to avert its complications. Keywords: cervical rib, somite, Hox gene